A Narrative Study on Exploring Google Voice Assistant in EFL Clasroom: Voice from Indonesian College Teacher - Wildana M. Giffari; Moh. Arif Mahbub; Moch. Imam Machfudi (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
In recent years, technology has played a crucial role in human life including education sector. The integration of artificial intelligence to the education sectors is an output of technology development. This study investigates the English foreign language college teachers’ experience in implementing the artificial intelligence based digital assistant called Google Voice Assistant (GVA). GVA was one of the types of digital assistant that was provide and dominantly used in Indonesia. This study seeks to an exploring of how collage teacher integrating the Google Voice Assistant in English foreign language classroom, especially for university students. This narrative study employs a semi- structured technique as a tool for exploring teachers experience towards the integrating of Google Voice Assistant. One willingness participant from private university in Jember, Indonesia was purposely selected based on research’s qualification and teacher availability that had experienced in implementing Google Voice Assistant in this area. The research findings showed the teacher had positive experience in the use of Google Voice Assistant that classify into five aspects. Comfortability, comprehension, usability, enjoyability, & worthwhileness. Although there some minor experience did appear in the aspect of usability and enjoyability, but in overall it can be conclude that Google Voice Assistant helps to facilitated teaching and learning language especially for English foreign language learners.